Analisis Pengeluaran Pemerintah Pusat dan Daerah - Maharani, Angelina; Pangestoeti, Wahjoe; Rini, Wa; Lestari, Indah Dwi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Government spending plays an important role in driving economic growth and improving people's welfare at the national and local levels. In the Indonesian context, both central and regional government spending has been analyzed to assess its impact on the economy and welfare. This spending includes infrastructure investments, social assistance, and improvements in public services, which significantly influence economic development. Studies show that well-managed spending can strengthen the economy, but if it is inefficient, it can have negative consequences. Analysis for 2024 shows a significant increase in the budget for various strategic sectors such as infrastructure, health, education and social. Although this spending aims to improve quality of life and economic growth, challenges such as diverse regional needs, financial constraints, and administrative coordination remain. Solutions such as administrative training and improved coordination are needed to ensure effective budget use. With the right strategy, government spending can be a major driver of economic growth and societal prosperity, although implementation challenges must continue to be overcome.